Mathematical modelling in education and culture: ICTMA 10 (Horwood Pub, 2003)
The mathematical modelling movement in mathematics education at school and university level has been influencing curricula for about 25 years. Lecturers will find material to enhance their teaching and extracurricular activities and educators will find innovative ideas to inform their course design and focus their research, while students will find interesting problems to explore. Helps lecturers enhance their teaching and extracurricular activitiesProvides educators with innovative ideas to inform their course design and focus their researchStudents will find interesting problems to explore
Includes bibliographical references. - Description based on print version record
Keywords: Electronic books; Congress; Electronic books -- Conference proceedings; Konferenzschrift